1984
DOI: 10.1002/1097-0142(19841101)54:9<1875::aid-cncr2820540918>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amino Acid Levels in Patients With Hepatocellular Carcinoma

Abstract: Serum amino acid concentrations in cirrhotic patients with and without hepatocellular carcinoma (HCC) were investigated. Elevation of serum aromatic amino acids (AAA) and methionine levels observed in cirrhotic patients without malignancy was not apparent in cirrhotic cases with HCC, and thus the ratio of branched chain amino acids (BCAA) to AAA was not so diminished in the latter cases. Development of hepatic encephalopathy in cirrhotic patients with HCC led to only a slight change in the serum aminogram char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 10 publications
4
41
0
1
Order By: Relevance
“…Taking under consideration the results from the study, prediction of tumour malignancy by assessment of sulphur-containing amino acids seems to be limited due to the fact that cysteine and cystine in serum were not evaluated. In opposition to the observations, the results of experimental studies on humans have shown that aromatic amino acid concentration increases in subjects suffering from neoplastic processes of the gastrointestinal tract, while BCAAs level decreases in such patients (13,17,31). Other data from research conducted on humans demonstrated changes in BCAAs concentration in patients with various neoplastic diseases, although total amino acid level was decreased (7,17,21).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Taking under consideration the results from the study, prediction of tumour malignancy by assessment of sulphur-containing amino acids seems to be limited due to the fact that cysteine and cystine in serum were not evaluated. In opposition to the observations, the results of experimental studies on humans have shown that aromatic amino acid concentration increases in subjects suffering from neoplastic processes of the gastrointestinal tract, while BCAAs level decreases in such patients (13,17,31). Other data from research conducted on humans demonstrated changes in BCAAs concentration in patients with various neoplastic diseases, although total amino acid level was decreased (7,17,21).…”
Section: Discussionmentioning
confidence: 91%
“…Due to a huge contribution of protein synthesis in growing tumours, it was found that the metabolism of sulphur-containing amino acids is most significantly influenced under such conditions. Thus, serum evaluation of amino acids may be considered as a valuable method for diagnosis and treatment of patients suffering from neoplastic diseases (19,20,30,31).…”
mentioning
confidence: 99%
“…Some studies have analyzed changes in certain amino acids in each type of tumor, in order to determine the influence of a particular tumor on the general metabolism of the patient, and occasionally to use as a diagnostic and therapeutic parameter [12][13][14][15][16][17][18] . Most of these studies, however, have included a low number of patients, with notable variations in their weight, clinical situation, tumor stage, and so on, all of which affect their reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced chronic liver disease, BCAA concentrations are low, whereas the concentrations of aromatic amino acids (AAAs) such as phenylalanine and tyrosine are high, a low Fisher ratio (BCAAs/AAAs) has been proven to a marker of liver disease progression, while a simplified Fisher ratio (BCAAs/tyrosine) predicts albumin levels at one year. [33][34][35] Several clinical trials have suggested that BCAA supplementation improves the prognosis of cirrhotic patients, and a recent review concludes that their supplementation improves nutritional status and quality of life in patients with advanced cirrhosis, and some international guidelines already recommend their use. 36 Another review of meta-analysis recommends oral administration of BCAAs in hepatic encephalopathy, especially in combination with nonabsorbable disaccharides.…”
Section: Malnutrition In Liver Cirrhosismentioning
confidence: 99%